Replication, Pathogenicity, Shedding, and Transmission of Zaire ebolavirus in Pigs - Gary Wong; Anders Leung; James Neufeld; Jason S. Richardson; Darryl Falzarano; Gregory A. Smith; Kevin Tierney; Ami Patel; Hana M. Weingartl (2011)
(See the editorial commentary by Bausch, on pages 179-81.)Reston ebolavirus was recently detected in pigs in the Philippines. Specific antibodies were found in pig farmers, indicating exposure to the virus. This important observation raises the possibility that pigs may be susceptible to Ebola virus infection, including from other species, such as Zaire ebolavirus (ZEBOV), and can transmit to other susceptible hosts.This study investigated whether ZEBOV, a species commonly reemerging in central Africa, can replicate and induce disease in pigs and can be transmitted to naive animals. Domesticated Landrace pigs were challenged through mucosal exposure with a total of 1 ×10(6) plaque-forming units of ZEBOV and monitored for virus replication, shedding, and pathogenesis. Using similar conditions, virus transmission from infected to naive animals was evaluated in a second set of pigs.Following mucosal exposure, pigs replicated ZEBOV to high titers (reaching 10(7) median tissue culture infective doses/mL), mainly in the respiratory tract, and developed severe lung pathology. Shedding from the oronasal mucosa was detected for up to 14 days after infection, and transmission was confirmed in all naive pigs cohabiting with inoculated animals.These results shed light on the susceptibility of pigs to ZEBOV infection and identify an unexpected site of virus amplification and shedding linked to transmission of infectious virus.